2020
DOI: 10.1681/asn.2019090964
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Structural Features from Living Donors Predict Graft Failure in the Recipient

Abstract: BackgroundNephrosclerosis, nephron size, and nephron number vary among kidneys transplanted from living donors. However, whether these structural features predict kidney transplant recipient outcomes is unclear.MethodsOur study used computed tomography (CT) and implantation biopsy to investigate donated kidney features as predictors of death-censored graft failure at three transplant centers participating in the Aging Kidney Anatomy study. We used global glomerulosclerosis, interstitial fibrosis/tubular atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 31 publications
(41 reference statements)
1
43
0
Order By: Relevance
“…26 Recipients of kidneys from living donors who have higher percentage IF/TA and larger cross-sectional tubular area are at a higher risk for graft failure. 27 Studies in patients with specific kidney diseases have also found measures of nephrosclerosis and nephron size to be predictive of progressive CKD. [28][29][30][31] This study demonstrates that in a population that does not have a specific kidney disease that would typically warrant a kidney biopsy (other than diabetic nephropathy and hypertensive nephrosclerosis), underlying larger nephron size and nephrosclerosis are predictors of progressive CKD.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recipients of kidneys from living donors who have higher percentage IF/TA and larger cross-sectional tubular area are at a higher risk for graft failure. 27 Studies in patients with specific kidney diseases have also found measures of nephrosclerosis and nephron size to be predictive of progressive CKD. [28][29][30][31] This study demonstrates that in a population that does not have a specific kidney disease that would typically warrant a kidney biopsy (other than diabetic nephropathy and hypertensive nephrosclerosis), underlying larger nephron size and nephrosclerosis are predictors of progressive CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This is a prospective cohort study of living kidney donors (aged !18 years) at the Mayo Clinic sites in Minnesota and Arizona from May 1, 1999, through December 31, 2018, in the Aging Kidney Anatomy Study. 18,19 Our inclusion criteria required a time-zero biopsy during the transplant surgery with 2 or more mm 2 of nondistorted cortex with at least 4 glomeruli. To study long-term kidney function outcomes, we targeted donors with 5 or more years of followup for participation.…”
Section: Study Design and Study Samplementioning
confidence: 99%
“…[14][15][16][17] They also modestly predict a lower postdonation glomerular filtration rate (GFR), albuminuria, and hypertension early after donation 18 and the death-censored risk for graft failure in the kidney recipient. 19 Long-term follow-up is needed to more fully comprehend the clinical importance of baseline microstructural features in the kidney at the time of donation. Thus, we performed a cohort study from the living donors in the Aging Kidney Anatomy study to determine whether nephron size, nephron number per kidney, or nephrosclerosis at the time of donation predict a long-term risk for developing low GFR, self-reported proteinuria, or hypertension.…”
mentioning
confidence: 99%
“…Kidney graft outcomes can be divided in short-term outcomes, such as early failure or one-year graft function, and long-term outcomes, such as (death-censored) graft failure and graft function decline [ 4 ]. Death-censored graft failure, as return to dialysis or re-transplantation, is seen in 10–12.5% of kidney transplant recipients at 5–6.2 years after transplantation [ 5 , 6 ]. Overall graft failure, including death with a functioning graft, is seen at a rate of 5% each year of follow-up, of which 40–60% is attributed to death with a functioning graft [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%